Solutions of a Class of Degenerate Kinetic Equations Using Steepest Descent in Wasserstein Space - Aboubacar Marcos; Ambroise Soglo (Journal of Mathematics)
We use the steepest descent method in an Orlicz–Wasserstein space to study the existence of solutions for a very broad class of kinetic equations, which include the Boltzmann equation, the Vlasov–Poisson equation, the porous medium equation, and the parabolic p-Laplacian equation, among others. We combine a splitting technique along with an iterative variational scheme to build a discrete solution which converges to a weak solution of our problem.